Physician characteristics and the physician-patient relationship. Impact of sex, year of graduation, and specialty. - Barnsley, J. (College of Family Physicians of Canada, 1999)
OBJECTIVE: To examine the association of physician sex, medical specialty, and year of graduation from medical school with attitudes and behaviours that define physician-patient relationships. Hypotheses tested are that women physicians, family physicians, and recent graduates spend more time discussing lifestyle and general health issues during patients' first visits; are more likely to report behaviours that are empathetic and that encourage communication with patients; are less likely to view their role as directive and problem-oriented; and are more supportive of patients' rights to information and participation in decision making. DESIGN: A survey was mailed to a stratified random sample of physicians between February and June 1996. SETTING: Physician practices in Ontario. PARTICIPANTS: Of 714 practising Ontario physicians, 405 (57%) responded. MAIN OUTCOME MEASURES: Proportion of time and actual time spent discussing a patient's lifestyle during a first visit, communication style, attitudes regarding a directive approach to care, and attitudes regarding patients' rights. RESULTS: Women physicians and family physicians spent significantly more time discussing lifestyle during a first visit. Women, family physicians, and recent graduates were significantly more likely to report an empathetic communication style. Women and recent graduates were significantly less likely to have a directive, problem-oriented approach to care. Family physicians were significantly less supportive of patients' rights than medical and surgical specialists were. CONCLUSIONS: Physicians in this study reported empathetic communication styles and attitudes that support information sharing and patients' rights.